Effect of soil properties on the response of pile to underground explosion - Jayasinghe, Laddu Bhagya (2015)
This paper develops and presents a fully coupled nonlinear finite element (FE) procedure to treat the response of piles to ground shocks induced by underground explosions. The Arbitrary Lagrange Euler coupling formulation is used in the study with proper state material parameters and equations. Pile responses in four different soil types, viz, saturated soil, partially saturated soil, and loose and dense dry soils are investigated and the results compared. Numerical results are validated by comparing them with those from a standard design manual. Blast wave propagation in soils, horizontal pile deformations, and damages in the pile are presented. Pile damage presented through plastic strain diagrams will enable vulnerability assessment of the piles under the blast scenarios considered. The numerical results indicate that the blast performance of single pile foundations embedded in saturated soil and loose dry soil are more severe than those embedded in partially saturated soil and dense dry soil. The present findings can serve as a benchmark reference for future analysis and design.